DETERMINING THE EFFECT OF DIABETES DURATION ON RETINAL AND CHOROIDAL THICKNESSES IN CHILDREN WITH TYPE 1 DIABETES MELLITUS. Issue 3 (March 2020) - Niestrata-Ortiz, Magdalena; Fichna, Piotr; Stankiewicz, Witold; Stopa, Marcin
Abstract : Purpose: Determining the effect of diabetes mellitus duration on retinal and choroidal thicknesses in children with Type 1 diabetes mellitus (T1DM). Methods: Children (aged 6–18 years) with Type 1 diabetes and no diabetic retinopathy and age-matched controls were examined using Topcon spectral domain optical coherence tomography. Choroidal thickness and retinal thickness in macula area were measured. The study group was divided into 3 subgroups depending on diabetes mellitus duration—Group 1: <5 years (n = 52), Group 2: 5 to 10 years (n = 39), and Group 3: >10 years (n = 30). Results: One hundred and twenty-one diabetic children and 32 controls were included. The central choroidal thickness increased from 305.5 μ m (SD: 61.7 μ m) in the control group to 309.2 μ m (SD: 70.1 μ m) in Group 1, 315.2 μ m (SD: 64.3 μ m) in Group 2, and 367.4 μ m (SD: 66.0 μ m) in Group 3. Group 3 differed significantly from Group 1 ( P = 0.0002), Group 2 ( P = 0.0014), and the control group ( P = 0.0003). The choroid-to-retina thickness ratio was lowest in controls, 1.01 (SD: 0.17), and highest in Group 3, 1.21 (SD: 0.2). Group 3 differed significantly from Group 1, Group 2, and the control group with P = 0.0002, P = 0.0014, and P = 0.0001, respectively. No retina thickening was found. Conclusion: Changes in the choroid may occur before the development of diabetic retinopathy and seem to progress with increasing diabetes mellitus duration despite the absence of diabetic retinopathy and without associated retina thickening. Choroidal thickness could be valuable for screening in diabetic children. Abstract : Our study demonstrates gradual thickening of the choroid in diabetic children without diabetic retinopathy with increasing duration of diabetes mellitus. This study encourages using choroidal thickness as a valuable screening parameter in diabetic children.